1982
DOI: 10.1055/s-0038-1657178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heparin Oligosaccharides with High Affinity for Antithrombin III in Experimental Venous Thrombosis

Abstract: SummaryThe in vitro and in vivo characteristics of two oligosaccharide heparin fragments have been compared to those of unfractionated mucosal heparin. A decasaccharide fragment had essentially no activity by APTT or calcium thrombin time assays in vitro, but possessed very high specific activity by anti-Factor Xa assays. When injected into rabbits at doses of up to 80 ¼g/kg, this fragment was relatively ineffective in impairing stasis thrombosis despite producing high blood levels by anti-Xa assays. A 16-18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 14 publications
5
60
0
1
Order By: Relevance
“…The specific antithrombotic activity of H, however, was more than an order of magnitude greater than that of h16 or h12, as expressed in both molar concentration and anti-Factor Xa activity, indicating that the antithrombotic effect of heparin in plasma does not only depend on its antiFactor Xa activity. This lack of correlation between the antithrombotic and anti-Factor Xa activity of heparin fragments confirms previous reports (21,27).…”
Section: Discussionsupporting
confidence: 92%
“…The specific antithrombotic activity of H, however, was more than an order of magnitude greater than that of h16 or h12, as expressed in both molar concentration and anti-Factor Xa activity, indicating that the antithrombotic effect of heparin in plasma does not only depend on its antiFactor Xa activity. This lack of correlation between the antithrombotic and anti-Factor Xa activity of heparin fragments confirms previous reports (21,27).…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent studies using purified antithrombin confirmed these trends, and it became clear that acceleration of inhibition of thrombin and FXa by heparin had different MW requirements (14,15). This difference was emphasised in studies by Holmer (16) and in our laboratory (17,18 ); high-affinity (for antithrombin) oligosaccharides with chain lengths mostly below 16 units, had very high anti-Xa activity, over 1,000 IU/mg, but their activity in thrombin inhibition and APTT assays was less than 10 IU/ mg.…”
Section: Mw Dependencementioning
confidence: 73%
“…The difference in the magnitude of the cofactor effect between heparin and the pentasaccharide was ϳ5-and ϳ60-fold for FXa in the absence and presence of Ca 2ϩ , and ϳ89-and ϳ74-fold for GDFXa in the absence and presence of Ca 2ϩ , respectively. These findings can explain why the anti-FXa activity of heparin exhibits a minimal chain length dependence in ex vivo and in vitro assays but significant chain length dependence in in vivo assays (16,17). …”
mentioning
confidence: 89%